Rationale and study design of the Prospective comparison of Angiotensin Receptor neprilysin inhibitor with Angiotensin receptor blocker MEasuring arterial sTiffness in the eldERly (PARAMETER) study. Issue 2 (4th February 2014) - Williams, Bryan; Cockcroft, John R; Kario, Kazuomi; Zappe, Dion H; Cardenas, Pamela; Hester, Allen; Brunel, Patrick; Zhang, Jack
Abstract : Introduction: Hypertension in elderly people is characterised by elevated systolic blood pressure (SBP) and increased pulse pressure (PP), which indicate large artery ageing and stiffness. LCZ696, a first-in-class angiotensin receptor neprilysin inhibitor (ARNI), is being developed to treat hypertension and heart failure. The Prospective comparison of Angiotensin Receptor neprilysin inhibitor with Angiotensin receptor blocker MEasuring arterial sTiffness in the eldERly (PARAMETER) study will assess the efficacy of LCZ696 versus olmesartan on aortic stiffness and central aortic haemodynamics. Methods and analysis: In this 52-week multicentre study, patients with hypertension aged ≥60 years with a mean sitting (ms) SBP ≥150 to <180 and a PP>60 mm Hg will be randomised to once daily LCZ696 200 mg or olmesartan 20 mg for 4 weeks, followed by a forced-titration to double the initial doses for the next 8 weeks. At 12–24 weeks, if the BP target has not been attained (msSBP <140 and ms diastolic BP <90 mm Hg), amlodipine (2.5–5 mg) and subsequently hydrochlorothiazide (6.25–25 mg) can be added. The primary and secondary endpoints are changes from baseline in central aortic systolic pressure (CASP) and central aortic PP (CAPP) at week 12, respectively. Other secondary endpoints are the changes in CASP and CAPP at week 52. A sample size of 432 randomised patients is estimated to ensure a power of 90% to assess the superiority of LCZ696 over olmesartan at week 12 in the change from baseline of mean CASP, assuming an SD of 19 mm Hg, the difference of 6.5 mm Hg and a 15% dropout rate. The primary variable will be analysed using a two-way analysis of covariance. Ethics and dissemination: The study was initiated in December 2012 and final results are expected in 2015. The results of this study will impact the design of future phase III studies assessing cardiovascular protection. Clinical trials identifier: EUDract number 2012-002899-14 and ClinicalTrials.gov NCT01692301 .